Innovation packages and scaling readiness workshop for smallholder famers mechanization starter pack, Zimbabwe: An activity report - Ijudai Jasada; Md Abdul Matin; Thierfelder, Christian; Mhlanga, Blessing; Louw-Nora, Hanke; Faju, Rose; Shiela Chikulo (International Maize and Wheat Improvement Center, 2023)
The smallholder mechanization starter pack is an innovation pioneered and developed by CIMMYT’s mechanization team in Zimbabwe. This tool was born out of necessity to alleviate farm power shortage faced by smallholder farmers and farming communities, offering a low-cost mechanization option centered on two-wheel tractor and small engine driven machinery pack. The pack is meticulously tailored to enhance land and labour productivity, improve timeliness of agricultural operations, reduce production cost, and eliminate human drudgery. The mechanization starter pack represents a significant shift from conventional, labor-intensive methodologies, aiming to elevate the agricultural landscape of Zimbabwe. Comprising a meticulously crafted two-wheel tractor, with auxiliary components such as ripper, multi-crop thresher, sheller, and trailer. The existing service delivery model involves prospective service providers (SPs) buying the starter pack from local manufacturers with funding acquired through various financing support including loans through a commercial bank (BancABC) or leasing through Ukama Ustawi or other projects. The SPs are delivering mechanization services across in their communities in rural Zimbabwe for a service fee.